2019
DOI: 10.7150/thno.32462
|View full text |Cite
|
Sign up to set email alerts
|

ZnAs@SiO2 nanoparticles as a potential anti-tumor drug for targeting stemness and epithelial-mesenchymal transition in hepatocellular carcinoma via SHP-1/JAK2/STAT3 signaling

Abstract: Rationale : Current therapies for hepatocellular carcinoma (HCC) are hampered by treatment failure and recurrence due to the remaining treatment-resistant liver cancer stem cells (CSCs). Stemness and epithelial-mesenchymal transition (EMT) are regarded as two fundamental characteristics of liver CSCs necessary for cancer progression; thus, drugs that simultaneously target both characteristics should prove effective in eliminating HCC and impeding recurrence. In this study, we developed new arsenic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…Moreover, correlation heat map indicated that the nine genes were highly relevant to miR-337-3p ( Fig. 4c) and STAT3 was selected for further study as previous evidence proved that it was targeted by miR-337-3p 29,30 , and played a crucial role in EMT 31 .…”
Section: Mir-337-3p Mediated Emt In 4t1 Cells By Directly Targeting Smentioning
confidence: 99%
“…Moreover, correlation heat map indicated that the nine genes were highly relevant to miR-337-3p ( Fig. 4c) and STAT3 was selected for further study as previous evidence proved that it was targeted by miR-337-3p 29,30 , and played a crucial role in EMT 31 .…”
Section: Mir-337-3p Mediated Emt In 4t1 Cells By Directly Targeting Smentioning
confidence: 99%
“…Different nanomaterials have been exploited to deliver synthetic chemotherapeutics and chemicals inside cancer cells reverting EMT and chemoresistance, and prevent metastasis in a plethora of tumor types [68][69][70][71][72][73][74][75][76][77][78].…”
Section: Synthetic Drugsmentioning
confidence: 99%
“…In this sense, zinc arsenite (ZnAs) NPs have been exploited as a molecular scaffold to deliver ATO in nasopharyngeal carcinoma (NCO) cells and hepatocarcinoma (HCC) tumor models [73,74]. ATO-loaded zinc arsenite (ZnAs) nanocomplexes inhibited EMT process via SHP-1/JAK2/STAT3 pathway and by reducing the expression of EMT-related proteins, leading to reduced tumor growth in vivo [73,74].…”
Section: Arsenic Trioxidementioning
confidence: 99%
“…Protein samples were then prepared from Hep3B cells with circ‐MALAT1 overexpression or empty vector and analyzed by western blot to verify the antibody‐array results. The most significantly increased protein correlated with circ‐MALAT1 overexpression was found to be Janus‐activated kinase 2 (JAK2), a well‐characterized protein that could induce CSC‐like characteristics (Figure C) . Conversely, Paired box 5 (PAX5), a tumor suppressor, decreased most significantly after circ‐MALAT1 overexpression among the 5 proteins (PAX5, ACTA1, ARFIP1, CLDN5, and KRT18) out of the 10 downregulated proteins in HCC cells (Figure D).…”
mentioning
confidence: 96%